Comparative Study of the Genetic and Biochemical Variability of Polyscias filicifolia (Araliaceae) Regenerants Obtained by Indirect and Direct Somatic Embryogenesis as a Source of Triterpenes - Anita A. Śliwińska (International Journal of Molecular Sciences, 2021)
Polyscias filicifolia (Araliaceae) is broadly used in traditional medicine in Southeast Asia due to its antimicrobial, immunomodulating and cytotoxic activities. The main groups of compounds responsible for pharmacological effects are believed to be oleanolic triterpene saponins. However, Polyscias plants demonstrate relatively slow growth in natural conditions, which led to applying a developing sustainable source of plant material via primary (PSE), secondary (DSE) and direct somatic embryogenesis from DSE (TSE). The AFLP and metAFLP genotyping resulted in 1277 markers, amplified by a total of 24 pairs of selective primers. Only 3.13% of the markers were polymorphic. The analysis of variance showed that the PSE and TSE regenerants differed only in terms of root number, while the DSE plantlets differed for all studied morphological characteristics. Further, the chemical analysis revealed that oleanolic acid (439.72 µg/g DW), ursolic acid (111.85 µg/g DW) and hederagenin (19.07 µg/g DW) were determined in TSE regenerants. Our results indicate that direct somatic embryogenesis ensures the production of homogeneous plant material, which can serve as a potential source of triterpene compounds. Plants obtained via somatic embryogenesis could also be reintroduced into the natural environment to protect and preserve its biodiversity.